2020
DOI: 10.1111/tmi.13401
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vaginal microbicides in preventing HIV transmission

Abstract: ObjectiveTo evaluate the evidence on the effectiveness of vaginal microbicides in preventing HIV transmission in women.MethodsSystematic review through a comprehensive search of relevant electronic databases for eligible randomised controlled trials (RCTs) published through June 2019. Two authors independently screened titles and abstracts according to eligibility criteria, then extracted data and assessed risk of bias of included studies. We conducted a random‐effects meta‐analysis of risk ratios (RR) of HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Several antiretroviral drugs are currently in advanced stages of development as microbicides, either vaginally or rectally (Al‐Khouja et al, 2020; Bunge et al, 2020; A. Y. Liu et al, 2019; MTN, 2020; Pleasants et al, 2020). However, there is no commercially available microbicide due to the lack of effectiveness of these products in preclinical and clinical trials for many reasons (Baeten et al, 2020; Musekiwa et al, 2020; Notario‐Perez et al, 2017).…”
Section: The Importance Of Vaginal Microbicides To Prevent Hiv‐1mentioning
confidence: 99%
“…Several antiretroviral drugs are currently in advanced stages of development as microbicides, either vaginally or rectally (Al‐Khouja et al, 2020; Bunge et al, 2020; A. Y. Liu et al, 2019; MTN, 2020; Pleasants et al, 2020). However, there is no commercially available microbicide due to the lack of effectiveness of these products in preclinical and clinical trials for many reasons (Baeten et al, 2020; Musekiwa et al, 2020; Notario‐Perez et al, 2017).…”
Section: The Importance Of Vaginal Microbicides To Prevent Hiv‐1mentioning
confidence: 99%
“…According to a systematic review of two Phase III trials (RING study 98 and ASPIRE study 99 ), a beneficial 29% reduction in HIV risk has been demonstrated with the intravaginal dapivirine ring (relative risk of 0.71; 95% CI 0.57–0.89). 100 Despite appearing to be less effective than oral PrEP, the vaginal ring represents an alternative for women who are unable to take oral PrEP according to the recommendations. Moreover, current developments are underway to include both contraception and HIV prevention in a single intravaginal ring.…”
Section: La-art Agents Based On Novel Pharmaceutical Formulationsmentioning
confidence: 99%
“…[ 104 ] However, PRO 2000 showed no evidence of efficacy against HIV in a clinical trial. [ 260 ] In vitro trials are not sufficient to indicate the antiviral activity of such materials in mammalian systems. Nonetheless, based on these observations, these materials can still be used for other applications like coatings, considering their direct interaction with the virus.…”
Section: Polymers Against Virusesmentioning
confidence: 99%